Microwave-assisted hydrothermal synthesis and characterization of ZnO nanorods - Ocakoglu, K.; Mansour, Sh. A.; Yildirimcan, S.; Al-Ghamdi, Ahmed A.; El-Tantawy, F.; Yakuphanoğlu, Fahrettin (Pergamon-Elsevier Science Ltd, 2015)
For the purpose of this study, the nanorods of zinc oxide were synthesized by rapid microwave-assisted hydrothermal route. The microstructure and surface morphology of the sensitized nanorods were characterized by X-ray diffraction (XRD), field emission scanning electron microscope (FE-SEM) and transmission electron microscope (TEM). XRD results indicate that synthesized ZnO nanorods have wurtzite phase. The calculated value of the particle size using Debye Scherrer formula and Williamson Hall plot was found to be 20-28 nm and 35.3 nm, respectively. Low uniformity distribution of rod-like morphology (60-80 nm in diameter and average length about 250 nm) are seen in TEM micrographs. The optical parameters of the prepared ZnO nanorods have been calculated using Kubeleka-Munk approach for the UV-vis diffuse reflectance spectrum. It is found that the direct transition optical band gap of the studied sample is 3.17 eV. The direct current electrical conductivity (sigma) was increased from 6.7 x 10(-8) to 3 x 10(-7) Omega(-1) cm(-1) with increasing the temperature (T) in the range (300-425 K). The obtained variation of a with T refers that the conductivity mechanism is controlled by thermally activated process. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: ZnO nanorods; Microwave-assisted hydrothermal; Diffuse reflectance; Optical properties